Pyrolysis of used sunflower oil in the presence of sodium carbonate by using fractionating pyrolysis reactor - Dandik, Levent; Aksoy, H.Ayşe (Elsevier BV, 1998)
Pyrolysis of used sunflower oil was carried out in a reactor equipped with a fractionating packed column (in three different lengths of 180, 360 and 540 mm) at 400 and 420°C in the presence of sodium carbonate (1, 5, 10 and 20% based on oil weight) as a catalyst. The use of packed column increased the residence times of the primer pyrolysis products in the reactor and packed column by the fractionating of the products which caused the additional catalytic and thermal reactions in the reaction system and increased the content of liquid hydrocarbons in gasoline boiling range. The conversion of oil was high (42–83 wt.%) and the product distribution was depended strongly on the reaction temperature, packed column length and catalyst content. The pyrolysis products consisted of gas and liquid hydrocarbons, carboxylic acids, CO, CO2, H2 and water. Increase in the column length increased the amount of gas and coke–residual oil and decreased the amount of liquid hydrocarbon and acid phase. Also, increase of sodium carbonate content and the temperature increased the formation of liquid hydrocarbon and gas products and decreased the formation of aqueous phase, acid phase and coke–residual oil. The major hydrocarbons of the liquid hydrocarbon phase were C5–C11 hydrocarbons. The highest C5–C11 yields (36.4%) was obtained by using 10% Na2CO3 and a packed column of 180 mm at 420°C. The gas products included mostly C1–C3 hydrocarbons.